Neohemigaster Malloch, 1939 and Pterogenia Bigot, 1859 (Diptera: Platystomatidae) from eastern Eurasia, with the description of four new species - Galinskaya, Tatiana V.; Shatalkin, Anatole I. (Zootaxa, 2013)
Four new species are described: Neohemigaster angustifrons sp.n. from Vietnam, Neohemigaster antropovi sp.n. from the Russian Far East, Neohemigaster tetralineata sp.n. from Taiwan and Pterogenia tenebrica sp.n. from Taiwan. In addition to Neohemigaster ussurica (Korneyev, 2001), six species formerly assigned to Pterogenia are transferred to Neohemi-gaster: Neohemigaster eurysterna (Hendel, 1914) comb. nov., Neohemigaster flavopicta (Hennig, 1940) comb. nov., Neohemigaster minuspicta (Hennig, 1940) comb. nov., Neohemigaster monticola (Frey, 1964) comb. nov., Neohemi-gaster ornata (Hennig, 1940) comb. nov., and Neohemigaster rectivena (Enderlein, 1924) comb. nov. A preliminary list of diagnostic characters separating the genera Pterogenia and Neohemigaster is compiled. A key to species of Pterogenia and Neohemigaster, known from Far East Russia, Japan, China, Taiwan, Vietnam and Burma, is provided.